2018
DOI: 10.1111/tri.13313
|View full text |Cite
|
Sign up to set email alerts
|

The impact of everolimus in reducing cytomegalovirus events in kidney transplant recipients on steroid-avoidance strategy: 3-year follow-up of a randomized clinical trial

Abstract: There is no evidence of whether everolimus (EVR) reduces cytomegalovirus (CMV) events in patients receiving steroid-free regimens. Besides, studies evaluating a tacrolimus (TAC) and EVR regimen are limited to 1-year follow-up. In this single-center prospective randomized trial, the incidence of CMV and 3-year efficacy and safety outcomes of EVR were compared to those of mycophenolate sodium (MPS) in a steroid-free regimen based on low-exposure TAC. Both groups received rabbit anti-thymocyte globulin (r-ATG) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Among the 61 included primary publications, the network analysis was based on 27 studies that evaluated graft loss or mortality. Of these, the formulation of TAC was named as Advagraf or Prograf in 9 studies [ 17 , 22 , 23 , 25 , 27 , 28 , 32 , 33 , 38 ], and the TAC formulation was not cited in the remaining 18 studies [ 39 , 42 , 44 , 45 , 48 50 , 52 62 ]. Figures 3 and 4 show the network diagrams for graft loss and mortality rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 61 included primary publications, the network analysis was based on 27 studies that evaluated graft loss or mortality. Of these, the formulation of TAC was named as Advagraf or Prograf in 9 studies [ 17 , 22 , 23 , 25 , 27 , 28 , 32 , 33 , 38 ], and the TAC formulation was not cited in the remaining 18 studies [ 39 , 42 , 44 , 45 , 48 50 , 52 62 ]. Figures 3 and 4 show the network diagrams for graft loss and mortality rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…15 In the last 5 years, several studies have posited that the use of EVR could reduce the incidence of CMV events posttransplant; however, further evidence is needed because CMV was not the primary endpoint, [13][14][15] or because of limitations in the previous study designs (e.g., use of the pp65 measure, single-center studies, and inclusion of D+R− and R + patients). [16][17][18] The strength and originality of the EVERCMV study is that it used a robust methodology to answer the research question, was multicentric, used a frequent monitoring of CMV QNAT calibrated with the World Health Organization international standard for CMV, and included a homogenous population of R+ KTRs.…”
Section: Discussionmentioning
confidence: 99%
“…However, across these studies (including the TRANSFORM trial), CMV events were not among the primary endpoints, there lacked a common monitoring protocol for CMV quantitative nucleic acid testing (QNAT) in KTRs, and neither the prophylaxis nor preemptive therapy protocols were standardized. Three single‐center trials with CMV infection as the primary endpoint showed a reduction of CMV infection and/or disease in R+ patients treated with everolimus (EVR) 16–18 . In these studies, CMV infection was mainly diagnosed with the pp65 antigenemia assay, which is less sensitive for detecting CMV compared to PCR 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously shown that EVR (3–8 ng/mL) is linked to comparable 3-y efficacy and a decreased incidence of cytomegalovirus (CMV) infection compared with MPA in patients receiving TAC (4–7 ng/mL), as part of an immunosuppressive regimen involving standard-dose rabbit antithymocyte globulin induction (6 mg/kg) and steroid-free maintenance. 3 This post hoc analysis presents the 5-y effectiveness and safety data from this trial.…”
mentioning
confidence: 99%